Approaches to forecast volcanic hazard in the Auckland Volcanic Field, New Zealand : a thesis presented in partial fulfilment of the requirements for the degree of Doctor of Philosophy in Earth Science at Massey University, Palmerston North, New Zealand - Kereszturi, Gabor (Massey University, 2014)
Monogenetic basaltic volcanism is characterised by a complex array of behaviours in the spatial distribution of magma output and also temporal variability in magma flux and eruptive frequency. For understanding monogenetic volcanoes different topographic and remote sensing-based information can be used, such as Digital Surface Models (DSMs). These data are most appropriately analysed in a Geographic Information System (GIS). In this study a systematic dataset of the Auckland Volcanic Field (AVF), New Zealand, was collected and pre-processed to extract quantitative parameters, such as eruptive volumes, sedimentary unit thicknesses, areas affected, spatial locations, and topographic positions. The topographic datasets available for the AVF were Shuttle Radar Topography Mission (SRTM), Advanced Spaceborne Thermal Emission and Reflection Radiometer (ASTER), contour-based Digital Elevation Models, and Light Detection And Range (LiDAR) datasets. These were validated by comparing their elevations to high accuracy ground control reference data from multiple Real-Time- Kinematic (RTK) Global Positioning System and Terrestrial Laser Scanning surveys. The attribute extraction was carried out on the LiDAR DSM, which had the best vertical accuracy of ≤0.3 m. The parameterisation of monogenetic volcanoes and their eruptive products included the extraction of eruptive volumes, areas covered by deposits, identification of eruptive styles based on their sedimentary characteristics and landform geomorphology. A new conceptual model for components of a monogenetic volcanic field was developed for standardising eruptive volume calculations and tested at the AVF. In this model, a monogenetic volcano is categorised in six parts, including diatremes beneath phreatomagmatic volcanoes, or crater infills, scoria/spatter cones, tephras rings and lava flows. The most conservative estimate of the total Dense Rock Equivalent eruptive volume for the AVF is 1.704 km3. The temporal-volumetric evolution of the AVF is characterised by a higher magma flux over the last 40 ky, which may have been triggered by plate tectonic processes (e.g. increased asthenospheric shearing and back-arc spreading underneath the Auckland region). The eruptive volumes were correlated with the sequences of eruption styles preserved in the pyroclastic record, and environmental influencing factors, such as distribution and thickness of water-saturated post-Waitemata sediments, topographic position, distance from the sea and known fault lines. The past eruptive sequences are characterised by a large scatter without any initially obvious trend in relation to any of the four influencing factors. The influencing factors, however, showed distinct differences between subdomains of the field, i.e. North Shore, Central Auckland and Manukau Lowlands. Based on the spatial variability of these environmental factors, a susceptibility conceptual model was provided for the AVF. Based on the comparison of area affected by eruption styles and eruptive volume, lava flow inundation is the most widespread hazard of the field. To account for this, a topographically adaptive numerical method was developed to model the susceptibility for lava flow inundation in the AVF. This approach distinguished two different hazard profiles for the valley-dominated Central Auckland and North Shore regions, and the flat Manukau Lowlands. A numerical lava flow simulation code, MAGFLOW, was applied to understand the eruption and rheological properties of the past AVF lava flow in the Central Auckland area. Based on the simulation of past lava flows, three eruptive volume-based effusive eruption scenarios were developed that best characterise the range of hazards expected. To synthesise, susceptibility mapping was carried out to reveal the patterns in expected future eruption styles of the AVF, based on the eruptive volumes and environmental factors. Based on the susceptibility map, the AVF was classified as highly susceptible to phreatomagmatic vent-opening eruptions caused by external environmental factors. This susceptibility map was further combined with eruptive volumes of past phreatomagmatic phases in order to provide an eruption sequence forecasting technique for monogenetic volcanic fields. Combining numerical methods with conceptual models is a new potential direction for producing the next generation of volcanic hazard and susceptibility maps in monogenetic volcanic fields. These maps could improve and standardise hazard assessment of monogenetic volcanic fields, raising the preparedness for future volcanic unrest.
Keywords: Volcanic activity prediction; Auckland Volcanic Field; Auckland; New Zealand